1994
DOI: 10.1017/s0022215100126416
|View full text |Cite
|
Sign up to set email alerts
|

Angioleiomyoma of the nasal cavity – report of a case and review of the literature

Abstract: Angioleiomyoma of the nasal cavity is an extremely rare tumour (Sawada, 1990). We present an unusual case of angioleiomyoma arising from the lateral wall of the nasal cavity without any symptoms of pain or epistaxis. Another unusual feature was that the tumour clinically resembled an inverted papilloma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 6 publications
0
23
0
1
Order By: Relevance
“…1 According to the literature, the most common symptoms are (considering the present case): nasal obstruction (56.25%), epistaxis (56.25%), facial pain (25%) and headache (25%). [1][2][3][4][6][7][8][9][10][11][12][13] Comparing literature data, we observed that the most frequent location of the vascular leiomyoma in the nasal cavity has been in the inferior turbinate. Of the 15 cases described (Table 1), 5 originated in the inferior turbinate; and as to symptoms, the initial complaint was nasal bleeding.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…1 According to the literature, the most common symptoms are (considering the present case): nasal obstruction (56.25%), epistaxis (56.25%), facial pain (25%) and headache (25%). [1][2][3][4][6][7][8][9][10][11][12][13] Comparing literature data, we observed that the most frequent location of the vascular leiomyoma in the nasal cavity has been in the inferior turbinate. Of the 15 cases described (Table 1), 5 originated in the inferior turbinate; and as to symptoms, the initial complaint was nasal bleeding.…”
Section: Discussionmentioning
confidence: 80%
“…1,8,11 At the time of diagnosis, the patients' ages ranged from 25 to 76 years, with an average of 55.6 years. 1,3,7,8,11 Radiologic studies, such as CT scan or MRI do not help much in diagnosis, however it is important to establish the extension of the lesion and treatment planning. 6 Treatment for these tumors is based on local resection, and there are no reports of recurrence after total excision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Morimoto (1973) classified these tumours histologically into three types: (i) capillary or solid, (ii) cavernous and (iii) venous. In the limbs, these tumours are mainly solid, while in the head and neck they are frequently of the venous type [8,9]. Histopathological differential diagnosis includes hemangioma, angiofibroma, fibromyoma, leiomyoblastoma, angiomyolipoma, vascular leiomyosarcoma [8].…”
Section: Discussionmentioning
confidence: 99%